Optimization and Efficiency of Energy Conversion Technology Integration in Hygiene Systems - Wibowo, Cahyo; Hasudungan, Herbert; Panalili T, Ojakma Sihar; Setiawan, Dibyo; Mubina Dewadi, Fathan (Public Health and Safety International Journal, 2025)
The integration of energy conversion technologies in hygiene systems plays a crucial role in enhancing energy efficiency and reducing overall power consumption. This study explores various approaches to optimizing energy conversion within hygiene applications, including heat recovery systems, biogas utilization, and solar energy integration. The findings indicate that the use of exhaust heat recovery in HVAC systems can reduce energy consumption by up to 25%, while biogas from organic waste can lower fossil fuel dependence by 30%. Additionally, the integration of solar energy in sterilization processes has been shown to increase efficiency by 40% in industrial settings. Moreover, the study highlights that combining multiple energy conversion technologies results in greater energy savings compared to standalone implementations. A system integrating heat recovery and solar energy, for instance, demonstrated a 50% reduction in energy consumption within industrial sanitation applications. Despite these advantages, challenges such as high initial investment costs and limited regulatory support hinder widespread adoption. The research emphasizes the need for an optimization-based approach that considers technical, economic, and regulatory aspects to maximize efficiency and sustainability. By addressing these factors, industries can enhance hygiene system performance while reducing operational costs and environmental impact. Future research should focus on developing specific optimization models for various industrial and medical sectors and assessing the long-term implications of implementing these technologies at scale.